The Ngarunghal Tradition in Sundanese Marriage - Salsabila Fajrina Dhia; Khoirul Hidayah; Ahmad Izzuddin (LPPM UIN Saizu Purwokerto, 2026)
The ngarunghal tradition is a customary practice in Sundanese society that regulates the prohibition of a younger sibling marrying before their older sibling without a certain form of respect. This study aims to analyse the function of the ngarunghal tradition as living law in the Miduana Traditional Village community and to examine this practice from the perspective of legal anthropology and maslahah mursalah theory. This study uses empirical research methods with a legal anthropology approach and is qualitative in nature. Data was obtained through field observations, in-depth interviews with traditional leaders, community leaders, and practitioners of the ngarunghal tradition (older siblings, younger siblings, and immediate family), as well as supporting documentation. The results show that the ngarunghal tradition functions as a customary norm that regulates family relations and maintains social harmony through a mechanism of deliberation and family agreement, including in determining the form and amount of gifts to be given to the older sibling who is being bypassed. This practice is adhered to by the community, mainly to avoid taboos and customary sanctions known as kabadi or katulak, which are understood as symbolic consequences for violating customs. From a legal anthropology perspective, belief in these sanctions acts as an effective social control mechanism, even though it is not formal in nature. From the perspective of maslahah theory, the ngarunghal tradition contains social benefits that are hajiyyah and 'ammah in nature, as it aims to maintain order, family harmony, and social balance in the community. However, this study also found the potential for a shift from benefit to injustice if the demands for gifts do not take into account the economic capacity of the younger sibling. Therefore, the ngarunghal tradition remains relevant to be preserved as long as it is carried out based on the principles of deliberation, fair agreement, and does not cause harm.